Jeff Vandermeer's southern reach trilogy: a reading in the context of the anthropocene - Amaral, George Augusto do (Literartes, 2022)
This article aims to analyze Jeff VanderMeer’s Southern Reach (2014) trilogy of speculative fiction novels, in the light of theories related to the Anthropocene, discussing how the themes and formal devices of these novels, such as estrangement and metafictionality, dialogue with climatic, ecological and philosophical issues, stimulatingmeditations on our contemporary reality and on the challenges of the environmental crisis.